Peri-Contrast Staining as a Marker of Stent Failure: Restenosis, Thrombosis, and Fracture - Fakilahyel S. Mshelbwala; Brittany Fuller; Khaldoon Alaswad; Mir B. Basir (Case Reports in Cardiology, 2021)
Peri-stent contrast staining (PSS), defined as contrast staining around the stent struts, has been identified as an indicator of future stent failure in first generation, sirolimus-eluting coronary stents. 1 PSS has been associated with in-stent restenosis, stent thrombosis, stent fracture, and the development of coronary aneurysm. As the frequency of patients with first generation sirolimus-eluting coronary stents becomes infrequent; PSS may go unrecognized. Herein, we present a patient with a decade of longitudinal follow-up, who developed PSS identified on coronary angiogram with recurrent stent failure.